Intelligent IoT and Dynamic Network Semantic Maps for more Trustworthy Systems - Lopes, Fábio Adriano Seixas (2018)
As technology evolves, the Internet of Things (IoT) concept is gaining importance for constituting a foundation to reach optimum connectivity between people and things. For this to happen and to allow easier integration of sensors and other devices in these technologic environments (or networks), the configuration is a key process, promoting interoperability between heterogeneous devices and providing strategies and processes to enhance the network capabilities. The optimization of this important process of creating a truly dynamic network must be based on models that provide a standardization of communication patterns, protocols and technologies between the sensors. Despite standing as a major tendency today, many obstacles still arise when implementing an intelligent dynamic network. Existing models are not as widely adopted as expected and semantics are often not properly represented, hence resulting in complex and unsuitable configuration time. Thus, this work aims to understand the ideal models and ontologies to achieve proper architectures and semantic maps, which allow management and redundancy based on the information of the whole network, without compromising performance, and to develop a competent configuration of sensors to integrate in a contemporary industrial typical dynamic network.